Application of Ultrasound-Guided Core Biopsy to Minimal-Invasively Diagnose Supraclavicular Fossa Tumors and Minimize the Requirement of Invasive Diagnostic Surgery. Issue 4 (January 2016) - Chen, Chun-Nan; Lin, Che-Yi; Chi, Fan-Hsiang; Chou, Chen-Han; Hsu, Ya-Ching; Kuo, Yen-Lin; Lin, Chih-Feng; Chen, Tseng-Cheng; Wang, Cheng-Ping; Lou, Pei-Jen; Ko, Jenq-Yuh; Hsiao, Tzu-Yu; et al.
Abstract : Abstract: Tumors of the supraclavicular fossa (SC) is clinically challenging because of anatomical complexity and tumor pathological diversity. Because of varied diseases entities and treatment choices of SC tumors, making the accurate decision among numerous differential diagnoses is imperative. Sampling by open biopsy (OB) remains the standard procedure for pathological confirmation. However, complicated anatomical structures of SC always render surgical intervention difficult to perform. Ultrasound-guided core biopsy (USCB) is a minimally invasive and office-based procedure for tissue sampling widely applied in many diseases of head and neck. This study aims to evaluate the clinical efficacy and utility of using USCB as the sampling method of SC tumors. From 2009 to 2014, consecutive patients who presented clinical symptoms and signs of supraclavicular tumors and were scheduled to receive sampling procedures for diagnostic confirmation were recruited. The patients received USCB or OB respectively in the initial tissue sampling. The accurate diagnostic rate based on pathological results was 90.2% for USCB, and 93.6% for OB. No significant difference was noted between USCB and OB groups in terms of diagnostic accuracy and the percentage of inadequate specimens. All cases in the USCB group had the sampling procedure completed within 10 minutes, but not in the OB group. No scars larger than 1 cm were found in USCB. Only patients in the OB groups had the need to receive general anesthesia and hospitalization and had scars postoperatively. Accordingly, USCB can serve as the first-line sampling tool for SC tumors with high diagnostic accuracy, minimal invasiveness, and low medical cost.